ANALISIS KOMPARASI QOS DAN QOE PROTOKOL VPN PADA JARINGAN REDISTRIBUSI RUTE OSPF EIGRP - Ariel Ramadhan Diva Aretha Putra Retnawan; ABDUS SALAM (LPPM Universitas Abdurrab, 2026)
The integration of OSPF and EIGRP dynamic routing through route redistribution aims to connect different domains, but it has the potential to cause routing loops and increased latency, thus requiring a Virtual Private Network (VPN) to protect data privacy and integrity. This research contributes as a study that systematically evaluates the QoS and QoE of three VPN protocols in an OSPF-EIGRP route redistribution environment, to fill a gap in the literature that was previously limited to static networks. Using the GNS3 simulator, PPTP, OpenVPN, and WireGuard were compared across three comprehensive scenarios: bandwidth measurement (iPerf3), file transfer of various formats (Seafile), and video streaming (HTML5). QoS parameters were evaluated based on the TIPHON standard, while QoE was measured using ITU-T G.107 to calculate the R-Factor and MOS. Wireshark analysis results show that WireGuard outperforms the others overall. In the bandwidth scenario, WireGuard achieved a transfer rate of 17.0 MB with a throughput of 14.0 Mbps. For file transfers, this protocol recorded the lowest delay of 32.27 seconds for document sized at 41.74 megabytes. and the highest throughput of 12.14 Mbps for images with minimal jitter. In the streaming scenario, WireGuard produced an R-Factor of 94.085 and a MOS of 4.421, falling into the “Very Good” and “Excellent” categories with no packet loss. In conclusion, WireGuard is recommended as the most optimal VPN protocol for securing dynamic network infrastructure with complex route redistribution.